Predictors of ribociclib-mediated antitumour effects in native and sorafenib-resistant human hepatocellular carcinoma cells - Reiter, Florian Paul; Itzel, Timo; Teufel, Andreas (Cellular oncology, 2019)
Purpose The cyclin-dependent kinases (CDKs) CDK4 and CDK6 are important regulators of the cell cycle and represent promising targets in cancer treatment. We aimed to investigate the relevance of CDK4/6 in the development of hepatocellular carcinoma (HCC) and the potential of ribociclib, a novel orally available CDK4/6 inhibitor, as a treatment for HCC. Methods The effect of ribociclib was assessed in native and sorafenib-resistant HCC cell lines using viability assays, colony formation assays and FACS-based analyses. The expression of potential biomarkers of ribociclib response was assessed in cell lines and primary human hepatocytes using Western blotting. In addition, the prognostic relevance of the cyclin D-CDK4/6-retinoblastoma protein (Rb) pathway was assessed by analysing mRNA expression data from The Cancer Genome Atlas (TCGA). Results We found that ribociclib downregulated Rb and caused a profound loss of cell viability by inducing G1 cell cycle arrest in HCC cell lines exhibiting Rb-high/p16-low protein expression profiles, but not in Rb-low/p16-high cells, regardless their sensitivity to sorafenib. siRNA-based Rb silencing decreased cell proliferation, but did not diminish the sensitivity of HCC cells to ribociclib. Furthermore, we found that ribociclib synergized with sorafenib to cause cell death. mRNA analysis of primary human HCC specimens showed that CDK4 expression was correlated with patient survival and that the expression of Rb and the p16-encoding CDKN2A gene were inversely correlated. Conclusions From our data we conclude that impairment of the cyclin D-CDK4/6-Rb pathway is a frequent feature of HCC and that it is associated with a unfavourable prognosis. We also found that ribociclib exhibits a preferential antineoplastic activity in Rb-high HCC cells. Our results warrant further investigation of Rb and p16 expression as markers of HCC sensitivity to ribociclib.
Gesehen am 18.10.2019